2007
DOI: 10.1007/s00417-007-0596-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of topical natural ergot alkaloids on the intraocular pressure and aqueous humor dynamics in oclular normotensive and α-chymotrypsin-induced ocular hypertensive rabbits

Abstract: Taken together, our data suggest that these compounds decrease both tonographic outflow facility and, to a greater extent, aqueous humor inflow, which explains their final effect in ocular normotensive and in alpha-chymotrypsin-induced ocular hypertensive rabbits. Reductions in aqueous humor inflow observed after topical application of natural ergot alkaloids in alpha-chymotrypsin-induced ocular hypertensive rabbits can only be explained by a marked inhibition of active secretion of aqueous humor, since proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…However, we expect the 0.46 µL/(minϫmm Hg) value to approximate the control outflow conductance of the normal sheep eye. This value is similar to that obtained in eyes of other species, eg, 0.2 to 0.4 µL/(minϫmm Hg) in rabbits 8,[16][17][18][19][20][21] and 0.3 µL/(minϫmm Hg) in humans. 22 As such, it is possible that anecortave reversed the increase in aqueous outflow resistance produced by prednisolone so that outflow conductance in the combined presence of the 2 agents was similar to that in the normal eye.…”
Section: Commentsupporting
confidence: 88%
“…However, we expect the 0.46 µL/(minϫmm Hg) value to approximate the control outflow conductance of the normal sheep eye. This value is similar to that obtained in eyes of other species, eg, 0.2 to 0.4 µL/(minϫmm Hg) in rabbits 8,[16][17][18][19][20][21] and 0.3 µL/(minϫmm Hg) in humans. 22 As such, it is possible that anecortave reversed the increase in aqueous outflow resistance produced by prednisolone so that outflow conductance in the combined presence of the 2 agents was similar to that in the normal eye.…”
Section: Commentsupporting
confidence: 88%
“…In the study, ergocristine, α-ergocriptine, and ergocornine were found to be effective in decreasing the IOP in a dose-dependent fashion, producing an ocular antihypertensive effect. The same group later conducted a comparative evaluation of the effect of these alkaloids on IOP and on aqueous humor dynamics, both in ocular normotensive and in α-chymotrypsin-induced ocular hypertensive rabbits [ 40 ]. The tested molecules decreased both tonographic outflow facility and aqueous humor inflow, which explains the reduction of the IOP in a dose-related fashion for both rabbit models.…”
Section: Role Of Ergot Alkaloids In Reducing Intraocular Pressurementioning
confidence: 99%
“…Similarly, antiurease, α -glucosidase, and antilipoxygenase activity is reported in the literature for crude alkaloids from fruit, bark, leaves, and root of Zanthoxylum armatum [ 41 ]. Alkaloids isolated from different plants were also investigated for their α -chymotrypsin inhibitory potential [ 42 – 44 ]. The above reported data support the urease α -chymotrypsin inhibitory activities of our alkaloids 1 – 4 .…”
Section: Resultsmentioning
confidence: 99%